Faktor – Faktor yang Berhubungan dengan Kejadian Dismenore Primer pada Remaja Putri di SMAIT Raflesia Depok Tahun 2024: Factors Related to The Incidence of Primary Dysmenorrhea in Adolescent Females at SMAIT Raflesia Depok in 2024 - Syafila; Imrar, Iin Fatmawati; Simanungkalit, Sintha Fransiske (Universitas Airlangga, 2024)
Background: Adolescence marks the onset of puberty, during which physiological and hormonal changes occur. In female adolescents, one of the primary indicators of puberty is the initiation of menstruation. During the menstrual phase, some adolescents experience lower abdominal pain, known as dysmenorrhea. Various factors, including body fat percentage and nutrient intake, have been identified as contributors to dysmenorrhea. Objectives: This study aimed to investigate the association between body fat percentage, fat intake, and the levels of iron, calcium, and magnesium intake on the incidence of primary dysmenorrhea among adolescent girls at SMAIT Raflesia Depok in 2024. Methods: The study was conducted in February 2024 at SMAIT Raflesia Depok, utilizing a quantitative, cross-sectional design. The sample comprised 103 female students from grades X and XI, aged 14 to 17 years, selected through stratified random sampling. Study variables included body fat percentage, fat intake, iron intake, calcium intake, magnesium intake, and the incidence of primary dysmenorrhea. Data were analyzed using the chi-square test. Results: Analysis revealed a significant association between iron intake (p-value=0.009), calcium intake (p-value=0.006), and magnesium intake (p-value=0.020) with the incidence of primary dysmenorrhea. However, no significant association was observed for body fat percentage (p-value=0.349) or fat intake (p-value=0.616). Conclusions: This study highlights a significant association between the intake of iron, calcium, and magnesium and the occurrence of primary dysmenorrhea among adolescent girls at SMAIT Raflesia Depok in 2024. These findings underscore the importance of maintaining a healthy body fat percentage and ensuring adequate nutritional intake to reduce the risk of dysmenorrhea in this population.